EPISTEMOLOGY OF RELIGIOUS MODERATION EDUCATION MAJELIS TAFSIR AL-QUR’AN (MTA) SURAKARTA - Mibtadin, Mibtadin; Masamah, Ulfa (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
The epistemology of MTA's religious moderation education is based on its existence as a religious movement that carries purification to invite Muslims to return to the Koran and hadith. By returning to these two sources all the problems of life can be answered. The epistemology of MTA religious moderation education is a religious attitude that does not blame others, lives together, and builds social harmony based on two things: first, not feeling the most right; and secondly, don't blame others. In the practice of religious moderation education, MTA is based on four indicators: first, national commitment to display symbols, identity, and respect for the flag, and to prioritize national values. Second, tolerance is understood in two ways, namely tolerance related to doctrines and teachings; second, tolerance related to the acceptance of other groups outside the MTA. The implication is that religious attitudes do not feel the most self-righteous; and do not blame other groups. Third, anti-violence, the MTA criticizes and rejects acts of violence based on religion, especially terrorism. Because it is not in line with the mission of sending the Messenger of Allah as a bearer of mercy and improving human character. Fourth, accommodating to local culture, Islam must be kaffah according to the Qur'an and Sunnah without adding values outside of itself, Islam is Islam and culture is culture. Islam and culture are two different things, both are single entities.